Study of Radiant Interference Based on Model of Electric Locomotive in Underground Tunnel - CHENG Qiang; LIU Jin-jiang; GUO Jin-liang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper put forward a finite element method to study the radio transmission in tunnel electromagnetic environment. The author makes use of software simulation to study the rectangular tunnel model.When varying the electric parameters of tunnel wall, ceiling and floor, this may somewhat influence the propagation characteristics of electromagnetic wave.In order to study the interference properties of underground electric locomotive ,this paper put forward a moment of method (MoM) model to analysis electromagnetic compatibility in roadway.The author makes use of FEKO software to simulate its time-varying and non-linear characteristics ,the simulation results are in good agreement with experimental data .In the end it can be concludeed that this model has practical significance to estimate electromagnetic interference in coal mine. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3253